Preconcentration and determination of Cu(II) and Cd(II) ions from wastewaters by using hazelnut shell biosorbent immobilized on Amberlite XAD-4 resin - Orhan Acar; İhsan Alacabey; Selma Akdeniz; Kadir Erol; İbrahim Teğin (MANAS: Journal of Engineering)
Hazelnut shell biosorbent immobilized on Amberlite XAD-4 polymer resin as solid phase extraction method was developed and used for preconcentration of Cu(II) and Cd(II) ions from aqueous solutions. Concentrations of analytes in solutions were determined by Flame Atomic Absorption Spectrometry after extraction with column technique. Functional groups of nutshell biosorbent immobilized on resin were characterized by Fourier transform infrared spectrometry. Optimized critical parameters for preconcentration of Cu2+ and Cd2+ ions from sample solutions with nutshell immobilized on the resin were the pH value of solution, type of eluent solutions, the flow rate of sample solution, quantities of nutshell biosorbent, Amberlite XAD-4 resin, and enrichment factors, respectively. Detection limits of Cu2+ and Cd2+ ions found were 0.29 μg L-1 and 0.25 μg L-1, respectively. The method proposed was applied for determinations of Cu2+ and Cd2+ ions in standard reference material (BCR-670 aquatic plant sample) for accuracy and applied to real water samples such as wastewater and Van lake water. At the 95% confidence level, relative standard deviations (RSDs) were found as 1.44% for Cd2+ and 1.21% for Cu2+ ions with three replicate measurements.